Study on Reuse of Coconut Fiber Chemical Retting Bath. Part 1: Retting Efficiency. Issue 5 (2nd September 2016) - Jose, Seiko; Mishra, L.; Basu, G.; Samanta, A. K.
ABSTRACT: Coconut husk is commonly retted in back water to extract coconut fiber. This retting takes about 10 months to complete and also pollutes the environment. A work on captive chemical retting of coconut fiber has carried out with NaOH, Na2 S, and Na2 CO3 . It is found that the residual retting liquor contains unreacted alkali, which is unutilized and might cause environmental issues, if not processed before disposal. An attempt has been made to estimate the residual alkali present in the residual waste liquor in order to reuse the retting bath by suitable addition of alkali. The physical parameters of the retted fibers were evaluated against raw fiber using standard methods. It is concluded that residual retting liquor could be used for further retting process by the addition of suitable quantity of chemicals.